2020
DOI: 10.31234/osf.io/5tmsh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chinese public’s knowledge, perceived severity, and perceived controllability of the COVID-19 and their associations with emotional and behavioural reactions, social participation, and precautionary behaviour: A national survey

Abstract: The outbreak of the coronavirus disease-19 (COVID-19) has caused enormous stress among the public in China. Intellectual input from various aspects is needed to control the COVID-19, including the understanding of the public’s emotion and behaviour and their antecedents from the psychological perspectives. Drawing upon the cognitive appraisal theory, this study examined three cognitive appraisals (i.e., knowledge, perceived severity and perceived controllability of the COVID-19) and their associations with a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
114
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 21 publications
11
114
6
2
Order By: Relevance
“…Li et al 19 conducted a study in China (n = 4,607) investigating the impact of people's behavior on COVID-19 containment measures. The authors focused on social participation, precautionary behavior, and perceived severity, among other behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 19 conducted a study in China (n = 4,607) investigating the impact of people's behavior on COVID-19 containment measures. The authors focused on social participation, precautionary behavior, and perceived severity, among other behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the present study, results of a study by Qian et al in China indicated that the perceived severity was an important predictor of corona prevention behaviors in China(31). Results of a research by Li et al also indicated that high perceived severity increased negative emotions, higher cellphone use, and caution in COVID-19(32). Furthermore, Kwok et al investigated the early stages of COVID-19 in Hong Kong and found that the individuals had higher perceived susceptibility and severity of COVID-19, so that 89 percent said that they were at risk for COVID-19 and 97 percent said that COVID-19 had severe symptoms(15).…”
mentioning
confidence: 96%
“…[25] The epidemic strengthens the determination of some rms to turn crises into opportunities and invest in new industries. It has strengthened consumers' health awareness and changed their consumption habits [26,27,28]. In the interview, some entrepreneurs expressed that this trend has brought new business opportunities and driving forces for marketing reform.…”
Section: The Responding Action Of Rmsmentioning
confidence: 99%